The Influence of Tourism Object Reconstruction and Tourist Visits on the Welfare of Mataram City Communities - Agustina, Ahadiah (Majapahit Journal of Islamic Finance and Management, 2024)
This research aims to analyze the influence of the reconstruction of tourist attractions and tourist visits on community welfare in the Mataram City area, Lombok. The method used in this research is a quantitative method with data analysis techniques using multiple linear regression. Data was collected through a questionnaire with a Likert scale consisting of 20 statements based on relevant indicators. The number of respondents in this study was 69 people, consisting of 30 men and 39 women. The results of multiple linear regression analysis show that the reconstruction of tourist attractions and tourist visits has a significant influence on the welfare of the people in Mataram City. The R-value obtained is 54.7%, which shows that the two independent variables together can explain 54.7% of the variation in community welfare. These findings indicate that increasing the quality and quantity of reconstruction of tourist attractions as well as the number of tourist visits can contribute positively to the welfare of local communities. This research provides practical implications for stakeholders in the tourism sector and local governments to continue to develop and improve tourist facilities and attract more tourists to improve community welfare. Furthermore, this research can be the basis for further studies that explore other factors that may influence the welfare of people in tourist areas.